Targeted nanoparticles modify neutrophil function in vivo - Völs, Sandra; Kaisar-Iluz, Naomi; Shaul, Merav E.; Ryvkin, Arik; Ashkenazy, Haim; Yehuda, Avishag; Atamneh, Ronza; Heinberg, Adina; Ben-David-Naim, Meital; Nadav, Menucha; Hirsch, Shira; Mitesser, Vera; et al. (Frontiers in Immunology, 2022)
Neutrophils play critical roles in a broad spectrum of clinical conditions. Accordingly, manipulation of neutrophil function may provide a powerful immunotherapeutic approach. However, due to neutrophils characteristic short half-life and their large population number, this possibility was considered impractical. Here we describe the identification of peptides which specifically bind either murine or human neutrophils. Although the murine and human neutrophil-specific peptides are not cross-reactive, we identified CD177 as the neutrophil-expressed binding partner in both species. Decorating nanoparticles with a neutrophil-specific peptide confers neutrophil specificity and these neutrophil-specific nanoparticles accumulate in sites of inflammation. Significantly, we demonstrate that encapsulating neutrophil modifying small molecules within these nanoparticles yields specific modulation of neutrophil function (ROS production, degranulation, polarization), intracellular signaling and longevity both in vitro and in vivo. Collectively, our findings demonstrate that neutrophil specific targeting may serve as a novel mode of immunotherapy in disease.